2023
DOI: 10.3758/s13414-023-02728-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effects of top-down attention and statistical learning during visual search: An EEG study

Abstract: The present study aims to investigate how the competition between visual elements is solved by top-down and/or statistical learning (SL) attentional control (AC) mechanisms when active together. We hypothesized that the “winner” element that will undergo further processing is selected either by one AC mechanism that prevails over the other, or by the joint activity of both mechanisms. To test these hypotheses, we conducted a visual search experiment that combined an endogenous cueing protocol (valid vs. neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…A study by Britton and Anderson (2020) examined whether learned spatial suppression established within the additional singleton paradigm transferred to a modified version of the spatial cueing paradigm, wherein a spatial cue predicted the location of an upcoming target character at chance level. The absence of transfer, as indexed via the cuing effect, observed in that study may not be surprising given that top-down attention generated by the cue arguably overrides any attentional bias implemented by statistical learning (Dolci et al, 2023), leaving it unclear whether suppression learned in one task remains in place in a different task setting. Nevertheless, there is reason to assume that this may be the case, as probability cueing studies (cf., Geng & Behrmann, 2002) have shown that learned facilitation does transfer between tasks.…”
Section: Transparency and Opennessmentioning
confidence: 74%
“…A study by Britton and Anderson (2020) examined whether learned spatial suppression established within the additional singleton paradigm transferred to a modified version of the spatial cueing paradigm, wherein a spatial cue predicted the location of an upcoming target character at chance level. The absence of transfer, as indexed via the cuing effect, observed in that study may not be surprising given that top-down attention generated by the cue arguably overrides any attentional bias implemented by statistical learning (Dolci et al, 2023), leaving it unclear whether suppression learned in one task remains in place in a different task setting. Nevertheless, there is reason to assume that this may be the case, as probability cueing studies (cf., Geng & Behrmann, 2002) have shown that learned facilitation does transfer between tasks.…”
Section: Transparency and Opennessmentioning
confidence: 74%